2022
DOI: 10.1111/jerd.12876
|View full text |Cite
|
Sign up to set email alerts
|

The resin bond to high‐translucent zirconia—A systematic review

Abstract: Objectives Several systematic literature reviews have assessed the scientific evidence on resin bonding protocols to conventional 3 mol% ytrria‐stabilized zirconia (3Y‐TZP) ceramics. It has been widely discussed, however, that the differing composition and physical properties of new high‐translucent zirconia generations (4Y‐TZP and 5Y‐TZP) may require alternative bonding materials and procedures. This paper reviewed in vitro studies on the success and durability of bonding protocols to high‐translucent zirconi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 146 publications
1
17
0
Order By: Relevance
“…The accuracy of 3D-printed models may be linked to the fact that they have little or no internal stresses owing to the layer-by-layer method of production of the cast. [23][24][25] Three strain gauges were placed on each side, two around each second premolar abutment on the buccal and distal sides, and the third one was on the edentulous ridge. This is in accordance with other studies that advocated a similar placement of strain gauges to monitor strains around abutments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of 3D-printed models may be linked to the fact that they have little or no internal stresses owing to the layer-by-layer method of production of the cast. [23][24][25] Three strain gauges were placed on each side, two around each second premolar abutment on the buccal and distal sides, and the third one was on the edentulous ridge. This is in accordance with other studies that advocated a similar placement of strain gauges to monitor strains around abutments.…”
Section: Discussionmentioning
confidence: 99%
“…For the retention of removable dental prostheses, there are currently several types of zirconia attachments available: an extracoronal attachment, a ball attachment for overdentures as a component of a zirconia post, and a bar attachment. [19][20][21][22][23] Recent advancements in computer-aided design and manufacturing (CAD/CAM) have made it possible to use zirconia for many dental restorations. Zirconia milling with CAD/CAM-controlled milling equipment is used to fabricate zirconia restorations.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure an adequate esthetic zone, a multilayer zirconia was used that mimics the color gradient from the incisal area to the cervical region, in addition, to further increase the esthetic characteristic, external stains and glazing were also applied to the restorations to acquire a more natural appearance. For UTML zirconia restorations fabricated with a minimally invasive approach, proper bonding is even more necessary 16,25,26 . Previous studies have shown that the final color of translucent monolithic zirconia is affected by material thickness and cement shade 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The same protocol can be applied on 3Y, 4Y and 5Y zirconia. Air abrasion followed by application of special primer with monomer 10-methacryloyloxydecyl dihydrogen phosphate (MDP) or composite resin cements containing MDP can lead to the long-term bond [73][74][75].…”
Section: Bonding To the Polycrystalic Ceramicmentioning
confidence: 99%